2008
DOI: 10.1194/jlr.m700602-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lipoxygenases and cyclooxygenases by linoleyl hydroxamic acid: comparative in vitro studies

Abstract: In this first comparative in vitro study, linoleyl hydroxamic acid (LHA), a simple and stable derivative of linoleic acid, was tested as an inhibitor of several enzymes involved in arachidonic acid metabolism in mammals. The tested enzymes were human recombinant 5-lipoxygenase (h5-LO), porcine leukocyte 12-LO, rabbit reticulocyte 15-LO, ovine cyclooxygenases 1/2 (COX1/COX2), and human microsomal prostaglandin E synthase-1 (mPGES-1). Potato tuber and soybean lipoxygenases (ptLOX and sLOX, respectively) were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Inhibition of potato lipoxygenase is through the possible formation of an Fe 3+ :LHA complex (Butovich and Reddy, 2002). The IC 50 values of LHA are over 3 orders of magnitude lower for certain lipoxygenases than cycloxygenases (Butovich and Lukyanova, 2008). Metal containing organic toxins have also been characterized and reported in the dinoflagellate, Pfeisteria piscicida (Moeller et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Inhibition of potato lipoxygenase is through the possible formation of an Fe 3+ :LHA complex (Butovich and Reddy, 2002). The IC 50 values of LHA are over 3 orders of magnitude lower for certain lipoxygenases than cycloxygenases (Butovich and Lukyanova, 2008). Metal containing organic toxins have also been characterized and reported in the dinoflagellate, Pfeisteria piscicida (Moeller et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…(Z,Z)-N-Hydroxy-9,12-octadecadienamide, linoleyl hydroxamic acid (LHA) displays biological activity as an inhibitor of lipoxygenases and cyclooxygenases, which are important enzymes in fatty acid metabolism and whose disruption is associated with several pathological states (Butovich and Reddy, 2002;Butovich and Lukyanova, 2008). Inhibition of potato lipoxygenase is through the possible formation of an Fe 3+ :LHA complex (Butovich and Reddy, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the PL effects on the enzymes from plant and animal sources can be explained comparing the affi nity of these enzymes to diversely charged phospholipids, which translocate to the mem- [50][51][52] brane through the same mechanism [19,24]. Affi nity to a particular lipid is associated with the enzyme localization in the cell.…”
Section: Phospholipidsmentioning
confidence: 99%
“…Another N-containing derivative of PUFAs is linoleyl hydroxamic acid (LHA). LHA was shown to be an inhibitor for pt5-LO [50], soybean 15-LO [52,60], porcine leucocytes 12-LO [51], rabbit reticulocyte 15-LO. Using the model system of mixed micelles with constant molar ratio, it was found that LHA acted as a noncompetitive inhibitor of pt5-LO.…”
Section: Polyunsaturated Fatty Acids (Pufas) and Their Derivativesmentioning
confidence: 99%
“…Linoleyl hydroxamic acid, studied as lipoxygenase inhibitor by Butovich and Lukyanova, was found to be effective against 15and 12-LOX. [36] Tepoxalin has been approved for the treatment of osteoarthritis in dogs. [37] Wong et al synthesized -aminohydroxamic acid derivatives, which are able to act as selective LTA 4 hydrolase inhibitors in vitro [38] (Figure 8).…”
Section: Tumour Necrosis Factor-alpha Converting Enzyme Inhibitorsmentioning
confidence: 99%